2020
DOI: 10.3390/plants10010011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight of Allantoin in Protecting Tomato Plants Against Ultraviolet C Stress

Abstract: Allantoin ((AT) a purine metabolite)-mediated ultraviolet C (UVC) stress mitigation has not been studied to date. Here, we reported the physicochemical mechanisms of UVC-induced stress in tomato (Solanum lycopersicum L.) plants, including an AT-directed mitigation strategy. UVC stress reduced plant growth and photosynthetic pigments. Heatmap and principal component analysis (PCA) revealed that these toxic impacts were triggered by the greater oxidative damage and disruption of osmolyte homeostasis. However, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 111 publications
1
25
0
Order By: Relevance
“…Heavy metals are chelated intracellularly by GSH, ASC, flavonoids, and certain ligands such as metallothioneins (MC) and phytochelatins (PC) to eliminate excessive buildup in plant cytosol [ 35 ]. Furthermore, non-enzymatic antioxidants can detoxify ROS and reduce oxidative stress in stressful situations [ 36 ]. In this study, we identified non-enzymatic antioxidants as well as several associated enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals are chelated intracellularly by GSH, ASC, flavonoids, and certain ligands such as metallothioneins (MC) and phytochelatins (PC) to eliminate excessive buildup in plant cytosol [ 35 ]. Furthermore, non-enzymatic antioxidants can detoxify ROS and reduce oxidative stress in stressful situations [ 36 ]. In this study, we identified non-enzymatic antioxidants as well as several associated enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the phenolic contents increased due to salinity stress. Phenolics are antioxidant compounds that contribute to the defense system and scavenge ROS induced by different stresses [ 55 ]. The activation of phenolics was further upregulated by exogenous treatment using NO sources.…”
Section: Discussionmentioning
confidence: 99%
“…3). This could be explained by the reduced level of the antioxidant allantoin, which is important in scavenging ROS (Brychkova et al , 2008 a ; Dawood et al , 2021) in Atxdh1 mutant leaves, resulting in lower antioxidant capacity under the applied stresses. Additionally, allantoin was shown to induce human wound skin healing by increasing collagen deposition (Araújo et al , 2010; Durmus et al , 2012), suggesting that allantoin accumulation after leaf wounding in Arabidopsis might heal at least in part, damaged plant cell wall and membranes.…”
Section: Discussionmentioning
confidence: 99%